2001
DOI: 10.1590/s0103-90162001000400008
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of host plants as a survival mechanism of leafhoppers Dilobopterus costalimai and Oncometopia facialis (Hemiptera: Cicadellidae), vectors of the Citrus Variegated Chlorosis (CVC)

Abstract: Dilobopterus costalimai (Young) and Oncometopia facialis (Signoret) are two of the most important species of citrus leafhoppers, vectors of bacterium Xylella fastidiosa which causes the Citrus Variegated Chlorosis (CVC) disease. To develop a rearing technique for these species under laboratory conditions, the egg laying preference and nymph development were studied in different breeding systems: Rangpur lime (Citrus limonia) and "falso boldo" (Vernonia condensata) as host plants. Trials were set up in a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
2
14
0
2
Order By: Relevance
“…Similar cases have previously been reported for H. vitripennis transmitting PD, as well as Dilobopterus costalimai and Oncometopia facialis spreading CVC (Milanez et al. ; Mizell et al. ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar cases have previously been reported for H. vitripennis transmitting PD, as well as Dilobopterus costalimai and Oncometopia facialis spreading CVC (Milanez et al. ; Mizell et al. ).…”
Section: Discussionsupporting
confidence: 83%
“…Milanez et al. () reported that alternation of host plants promoted a survival mechanism of the leafhoppers Dilobopterus costalimai Young and Oncometopia facialis (Signoret). Lauzière and Sétamou () reported that different host plants were necessary for oviposition and development of H. vitripennis .…”
Section: Introductionmentioning
confidence: 99%
“…The continual shift in host plant selection may be critical to this species as a survival mechanism to counter host plant variations in xylem composition. Milanez et al (2001) in Brazil reported similar alternative host selection behavior in two other cicadellids, Dilobopterus costalimai Young and Oncometopia facialis (Signoret), transmitting X. fastidiosa in citrus. In another study, Milanez et al (2003) reported 40 Ð 62% mortality in adult males and females D. costalimai and O. facialis caged on potted sweet orange, Citrus sinensis (L.), for 96 h (no-choice test situation).…”
Section: Discussionmentioning
confidence: 74%
“…Citrus are not primary but occasional hosts for them, while other alternative host plants are also important for the development of the different cicadomorphan species (Milanez et al 2001). This may explain why the number of collected insects was so low in some months during the sampling.…”
Section: Resultsmentioning
confidence: 99%